Planning Analysis and Efficiency Comparison of On-Grid, Off-Grid, and Hybrid Grid-Tied Rooftop Solar Power Systems for the Development of the Control Building of Perum Jasa Tirta 1/3, WS Brantas Division - Nindia Nova Novena; Royb Fatkhur Rizal (Universitas Proklamasi 45, 2026)
Perum Jasa Tirta I, WS Brantas Division in the Tulungagung working area, experiences unreliable electricity supply due to frequent outages, requiring an alternative solution through a rooftop photovoltaic (PV) system. This study aims to design and evaluate the performance and techno-economic feasibility of three configurations: On-Grid, Off-Grid, and Hybrid Grid-Tied systems. Based on the energy consumption analysis, the total demand is 233.5 kWh/day or 85,192.10 kWh/year. By considering system losses of 25% and an Equivalent Sun Hours (ESH) value of 4.5 hours/day, the required PV capacity is 69.18 kW, using 93 modules of 750 Wp. Simulation results using Homer Pro show that the On-Grid system generates 166,208 kWh/year, the off-grid system produces 123,361 kWh/year, and the hybrid grid-tied system generates 140,699 kWh/year. All systems are capable of meeting the load demand, with different levels of energy surplus. From a techno-economic perspective, the off-grid system provides the highest return with an NPV of IDR 11.2 billion and an IRR of 128%, but it is relatively overdesigned and highly dependent on batteries. The on-grid system offers lower investment costs but depends on the utility grid. Meanwhile, the hybrid system shows balanced performance and is considered the optimal solution.